Physical Properties and Sensory Quality of Roasted Meltique Beef Injected with PalmOil - D. Y. Yudantara; A. Apriantini; C. Budiman; N. C. Dainy; W. Humayrah (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Meltique beef was created by injecting vegetable oil emulsions into regular beef, but the high cost andoxidation susceptibility of canola oil limit its practicality. Palm oil, characterized by higher stabilityand local availability, was explored to improve physical properties and sensory qualities. The aim ofthis reserach was to analyze physical properties and sensory quality of roasted meltique beef injectedwith palm oil emulsion. Brahman cross sirloin cuts were injected with emulsions comprising oil, water,and soy protein isolate, prepared with different concentrations. The injected meats were grilled for 10minutes and assessed for pH, texture, cooking loss, and sensory attributes. Results showed that palm oilsignificantly enhanced texture and sensory properties, with palm oil at higher concentration being themost similar to Wagyu beef in marbling, tenderness, and flavor. The findings indicate that palm oil wasa cost-effective and stable alternative to canola oil for producing high-quality meltique beef, offering aviable solution for enhancing local beef products.